2009
DOI: 10.1038/ajh.2009.79
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Tumor Necrosis Factor Receptor 1 Level Is Associated With Left Ventricular Hypertrophy: The Northern Manhattan Study

Abstract: BACKGROUND Although inflammatory markers may be associated with risk of cardiovascular events, few data are available regarding these markers and their association with left ventricular hypertrophy (LVH). We sought to evaluate whether inflammatory markers were independently associated with LVH in a multiethnic population in northern Manhattan. METHODS A population-based cross-sectional study was conducted in 660 participants without stroke, who had undergone both transthoracic echocardiography and testing fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Soluble TNFR1 was shown to be cross-sectionally associated with cardiometabolic risk factors in a study of patients with coronary artery disease: elevated uric acid levels, lower HDL cholesterol, metabolic syndrome, diabetes and heart failure [21]. In accordance with our findings where sTNFR1 was associated with cardiovascular mortality after adjustments for CRP and IL-6, sTNFR1 but not IL-6 and CRP was associated with left ventricular mass in a study of over 600 patients with stroke [22]. Elevated levels of sTNFR1 and STNFR2 have also been associated with incident coronary heart disease in women with a low kidney function [23,24], and elevated levels of sTNFR2 were associated with incident coronary heart disease independently of hyperglycemia a 10-year follow-up of almost one thousand nurses with diabetes [25].…”
Section: Comparisons With Previous Studiessupporting
confidence: 87%
“…Soluble TNFR1 was shown to be cross-sectionally associated with cardiometabolic risk factors in a study of patients with coronary artery disease: elevated uric acid levels, lower HDL cholesterol, metabolic syndrome, diabetes and heart failure [21]. In accordance with our findings where sTNFR1 was associated with cardiovascular mortality after adjustments for CRP and IL-6, sTNFR1 but not IL-6 and CRP was associated with left ventricular mass in a study of over 600 patients with stroke [22]. Elevated levels of sTNFR1 and STNFR2 have also been associated with incident coronary heart disease in women with a low kidney function [23,24], and elevated levels of sTNFR2 were associated with incident coronary heart disease independently of hyperglycemia a 10-year follow-up of almost one thousand nurses with diabetes [25].…”
Section: Comparisons With Previous Studiessupporting
confidence: 87%
“…Inflammation is one possible link, as a DT has been shown to be associated with lower levels of inflammatory markers 13-15 . A prior study in this cohort found that levels of TNF receptor 1 were associated with LV mass and LV hypertrophy 16 . In the current study a DT was inversely associated with several important vascular risk factors associated with LV mass, most notably obesity.…”
Section: Discussionmentioning
confidence: 62%
“…Elevated TNFR1 levels were associated with lower MMSE score in our cohort, but we did not confirm that the relationship between MetS and MMSE score was mediated through inflammation, as suggested by other studies [34] . Elevation of TNFR1 has also been associated with decreased memory performance [35] and it may be a reflection of the inflammatory mechanisms operative in atherosclerotic disease as it has been shown to be associated, in our cohort and others, with increased carotid plaque [36] , left ventricular hypertrophy [16] and vascular dementia [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Serum amyloid A (SAA) and high-sensitivity C-reactive protein (hsCRP) were measured using the BNII nephelometric assay system (Dade-Behring, Deerfield, Ill., USA) [15] . Interleukin-6 (IL-6) and tumor necrosis factor receptor 1 (TNFR1) were measured by enzyme-linked immunosorbent assays according to manufacturer instructions (BioSource International, Camarillo, Calif., USA), as previously described [16] .…”
Section: Laboratory Assessmentsmentioning
confidence: 99%